Building games to exercise Computational Thinking in children on the autism spectrum through pre-defined templates and End-User Development concepts - Malpartida, Katherin Felipa Carhuaz; Rodrigues, Kamila Rios da Hora (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2024: Anais do XXXV Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2024.243251, 2024)
Computational Thinking (CT) is a reasoning process focused on solving problems, promoting the development of cognitive skills. Serious games can contribute to exercising these skills, as they are playful and adaptable tools for different audiences. This paper presents the design and evaluation of a Web template for building serious digital games to help improve the cognitive skills of children with Autism Spectrum Disorder (ASD), based on the fundamental principles of PC. The first phase of the Web template design was completed and evaluated by Education professionals from a partner institution. The observations and feedback collected are being discussed with the development and research teams to implement the functional version of the game.